2013
DOI: 10.1186/1916-0216-42-24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the timing of injection laryngoplasty for vocal fold paralysis in an attempt to avoid future type 1 thyroplasty

Abstract: ObjectivesTo determine whether immediate (less than 3 months from time of nerve injury), early (from 3 to 6 months from time of nerve injury) or late (more than 6 months from time of nerve injury) vocal fold injection influences the long-term outcomes for patients with permanent unilateral vocal fold paralysis.MethodsA total of 250 patients with documented unilateral vocal fold paralysis were identified in this retrospective chart review. 66 patients met the inclusion criteria, having undergone awake trancervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 16 publications
2
46
0
1
Order By: Relevance
“…In this regard, recent investigations have suggested that early postoperative management of VCP is advantageous [7,9,16]. Previous studies indicated that injection laryngoplasty using temporary injectable material in the acute postoperative period was safe and effective in preventing aspiration pneumonia in patients with VCP following thoracic surgery [8,17,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, recent investigations have suggested that early postoperative management of VCP is advantageous [7,9,16]. Previous studies indicated that injection laryngoplasty using temporary injectable material in the acute postoperative period was safe and effective in preventing aspiration pneumonia in patients with VCP following thoracic surgery [8,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Friedman et al suggested that early medialization creates a more favorable vocal cord position for phonation, which can be maintained during synkinetic reinnervation [7]. Alghonaim et al reported that use of temporary material for early medialization of a permanently paralyzed, abducted vocal fold appeared to diminish the likelihood of requiring permanent laryngeal framework SD standard deviation, MPT maximal phonation time, NHR noise-to-harmonics ratio, GRBAS grade of hoarseness, roughness, breathiness, asthenia, and strain, VHI voice handicap index surgery [9]. Furthermore, a recent meta-analysis examining the treatment of unilateral vocal cord paresis or paralysis after thyroidectomy proved that early injection is more effective than late injection, as demonstrated by a lower effect size for likelihood of an unsatisfactory outcome in the early injection group [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unilateral vocal cord palsy, if temporary, is known to recover completely by 9 to 12 months and can be aided by speech therapy and temporary medialization by injection laryngoplasty. In cases with permanent paralysis, attempts are directed at improving the voice, 3 Reiter and Brosch, 4 and Algonaim et al 5 have reported the mean age of their study cohort in the sixth decade of life, a decade more than our study. The difference in the age distribution between Indian and Western nations could be explained based on the higher life expectancy in the population of the affluent nations.…”
Section: Discussionmentioning
confidence: 46%
“…In medialization laryngoplasty, a common surgical approach, the vocal fold is paralyzed using an external approach. However, this procedure is fully invasive and has significant complications, especially if the surgeon is inexperienced (11).…”
Section: Introductionmentioning
confidence: 99%